2016
DOI: 10.5603/ait.a2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension complicating pancreatitis-induced acute respiratory distress syndrome in three patients on extracorporeal membrane oxygenation

Abstract: Background: Severe acute pancreatitis is associated with sever multiorgan failure from 15 to 50%, depending on the series. In some of these patients, conventional methods of ventilation and respiratory support will fail, demanding the use of extracorporeal membrane oxygenation (ECMO). Abdominal compartment syndrome is potentially harmful in this cohort of patients. We describe the successful treatment of three patients with severe acute pancreatitis who underwent respiratory ECMO and where intra abdominal pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
6
4
Order By: Relevance
“…The patients in our study were on ECMO support for a mean of 7.5 days, this compares to 9.3 days in the study by Guirand et al, although shorter average ECLS durations of 5 days have been reported. [12][13][14]17,32,35 Our study's total hospital length of stay also appears to be shorter, at 23.5 days, this compares to 25-40 days in previous studies. [12][13][14]17,32,35 Our hypothesized contributor to this survival is the emphasis on euvolemia, or net zero cumulative fluid balance (CFB) during daily multidisciplinary rounds.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…The patients in our study were on ECMO support for a mean of 7.5 days, this compares to 9.3 days in the study by Guirand et al, although shorter average ECLS durations of 5 days have been reported. [12][13][14]17,32,35 Our study's total hospital length of stay also appears to be shorter, at 23.5 days, this compares to 25-40 days in previous studies. [12][13][14]17,32,35 Our hypothesized contributor to this survival is the emphasis on euvolemia, or net zero cumulative fluid balance (CFB) during daily multidisciplinary rounds.…”
Section: Discussioncontrasting
confidence: 44%
“…14,17,[19][20][21] Adult Respiratory Distress Syndrome can also complicate the course of many acute care surgery pathologies, the most studied among them being acute pancreatitis, where it affects up to 30% of patients. 13 In patients with severe ARDS, there is a high mortality risk with conventional treatment. [12][13] Extracorporeal membrane oxygenation has been described in the trauma and surgical populations with promising results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 SAP complicated by IAH is prone to sepsis and respiratory failure. 3,4 SAP is one of the most common reasons for respiratory failure, whereas IAH precipitates exudation of pulmonary alveoli. SAP results in a longer length of hospitalization and higher mortality of sepsis.…”
Section: Introductionmentioning
confidence: 99%